La nulidad jurídica y la Jurisdicción Constitucional en el sistema legislado - Herrera Gómez, Ana Lucía; Martínez Marulanda, Diego; Restrepo Morales, Jorge (Estudios de Derecho, 1998)
La nulidad jurídica y la Jurisdicción Constitucional en el sistema legislado